Leak detection methods on main pipelines (Международный научный журнал «Инженер», 2026)
This article discusses methods for detecting leaks on main pipelines. The purpose of this work is to review upto-date information on leak detection methods on main pipelines, classification according to several criteria,according to the principle of operation, according to the method of recognition and responsiveness. Anoverview of existing leak detection methods, the negative pressure wave method, the volume balance methodin comparison of the volume of a substance entering the system, the pressure profile analysis method, andmonitoring of changes in pressure inside the pipeline in different sections are considered.